Red blood cell-derived microparticles induce kidney injury by triggering endothelial cell ferroptosis in intravascular hemolysis - Yao An; Hongyu Zhang; Danfeng Hu; Jingqiu Zhang; Qi Liu; Caixu Liu; Meishan Yan; Siqi Li; Minghui Xu; Chunyan Gao (Redox Biology, 2025)
Intravascular hemolysis is a common event in the pathogenesis of numerous diseases with heterogeneous etiologies and clinical features. A frequent adverse effect of massive hemolysis is kidney injury, which is a major cause of increased morbidity and mortality in chronic hemolytic diseases. However, the role of crosstalk between red blood cell-derived microparticles (RMPs) and endothelial cells (ECs) in hemolysis remains unknown, especially in hemolysis-mediated kidney injury. To answer this question, we established an in vitro co-incubation model of hemolysis-derived RMPs and ECs as well as a mouse model intravenously injected with hemolytic RMPs. We found that a large number of internalized RMPs contributed to the ferroptosis of ECs via iron overload, amino acid metabolism disorder, and the miR-130a/ACSL4 axis. Furthermore, RMPs-induced endothelial ferroptosis could enhance oxidative stress, aggravate histopathological damage, and promote loss of renal function in mice. These pathological effects were significantly ameliorated in mice treated with ferroptosis inhibitors ferrostatin-1 (Fer-1) and deferoxamine (DFO). In conclusion, our study demonstrated that RMPs-induced ferroptosis of ECs plays an important role in the development and progression of kidney damage associated with hemolysis, and inhibition of ferroptosis may be a potential therapeutic approach to prevent renal injury in patients with severe hemolytic crisis.